Dynamic precipitation and recrystallization mechanism during hot compression of Mg-Gd-Y-Zr alloy - Qian Zhang; Quanan Li; Xiaoya Chen; Jiaxin Zhao; Jian Bao; Ziyi Chen (Journal of Materials Research and Technology, 2021)
Hot compression tests of Mg-Gd-Y-Zr alloy at different deformation temperatures and strains were carried out with Gleeble-1500 simulator at strain rate of 0.002 s−1. The microstructure evolution of 400 °C/0.002 s−1 sample under different strain was analyzed emphatically by transmission electron microscopy and electron backscatter diffraction technology. Dynamic precipitation characteristics and nucleation-expansion mechanism of dynamic recrystallization (DRX) were discussed in detail. The results indicated that the dynamic precipitation takes place prior to DRX, and the morphology, size and distribution of precipitates change with increasing strain. At the later stage of deformation, the large-size hard phase β-Mg5(Gd,Y) can induce the particle-stimulated nucleation (PSN) mechanism under large strain and act as an effective nucleation site for DRX. In addition, we constructed a schematic diagram of the DRX nucleation-expansion mechanism of Mg-Gd-Y-Zr alloy under high temperature deformation. The first layer of DRX grains is formed by discontinuous dynamic recrystallization (DDRX) mechanism characterized by grain boundary bulge out, and the precipitates distributed at the original grain boundary promote DDRX nucleation; The expansion of necklace structure depends on continuous dynamic recrystallization (CDRX) mechanism; Subgrain division can further refine DRX grains.